Diagnostic Significance of Paraneoplastic Neuronal Antibodies in Japanese Adults with Autoimmune Encephalitis: A Case Series Study in an Adult Epilepsy Clinic - Kinoshita M; Takada K; Ohara H; Sai T; Elangovan A; Suresh Babu HW; Vellingiri B; Satow T (Clinical Pharmacology: Advances and Applications, 2025)
Masako Kinoshita,1 Kozue Takada,1 Hiroya Ohara,2 Toshi Sai,3 Ajay Elangovan,4 Harysh Winster Suresh Babu,4 Balachandar Vellingiri,4 Takeshi Satow5 1Department of Neurology, National Hospital Organization Utano National Hospital, Kyoto, Japan; 2Department of Neurology, Minaminara General Hospital, Yoshino, Nara, Japan; 3Department of Neurology and Stroke Treatment, Japanese Red Cross Kyoto Daiichi Hospital, Kyoto, Japan; 4Department of Zoology, Central University of Punjab, Bathinda, PB, India; 5Department of Neurosurgery, National Hospital Organization Utano National Hospital, Kyoto, JapanCorrespondence: Masako Kinoshita, Department of Neurology, National Hospital Organization Utano National Hospital, 8 Ondoyama-Cho, Narutaki, Ukyoku, Kyoto, 616-8255, Japan, Tel +81-75-461-5121, Fax +81-75-464-0027, Email machak@kuhp.kyoto-u.ac.jpPurpose: Recently, the role of autoimmune mechanisms in epileptogenesis and intractability has attracted attention. The clinical features of autoimmune encephalitis (AE) vary; thus, diagnosis can be difficult and often delayed. Paraneoplastic neurological syndromes are usually associated with malignant cancers; however, paraneoplastic antibodies (PAs) can be present in the absence of overt cancers. In this single-center, retrospective study, we evaluated the diagnostic significance of PAs in adult Japanese patients with AE.Patients and Methods: We retrospectively analyzed the medical records of all patients who visited our epilepsy clinic and underwent a thorough diagnostic evaluation for AE between April 2021 and October 2022. Patients who met the criteria for AE and presented to our epilepsy clinic with new-onset seizures or acute or subacute seizure aggravation were included. Data from the PA panel, including anti-amphiphysin (AMPH), CV2, paraneoplastic Ma antigen 2 (PNMA2), Ri, Yo, Hu, recoverin, SRY-related HMG-box gene 1 (SOX1), titin, zic4, glutamate decarboxylase 65 (GAD65), and Tr/DNER antibodies, were evaluated.Results: Of 32 patients who were investigated, 6 (19.0%; 2 males, age: 38.0 ± 18.0 years) were positive for PAs (anti-AMPH: 1, PNMA2: 1, Yo: 1, recoverin: 2, SOX1: 1). No patients had malignant tumors. Serum anti-SS-A/Ro antibodies were detected in one patient, and the cerebrospinal fluid showed a slightly elevated protein level. Intravenous high-dose methylprednisolone was administered to four patients and was effective in three.Conclusion: Approximately one-fifth of AE cases were attributable to PAs, although there were no signs of malignant tumors, in adult epilepsy clinics in Japan.Plain Language Summary: Epilepsy affects more than 70 million people worldwide; however, its etiology remains unknown in approximately one-third of patients. Recently, autoimmune mechanisms of epilepsy have gained attention. However, diagnosing autoimmune encephalitis (AE) remains difficult, because patients with AE can show various symptoms. Paraneoplastic antibodies (PAs) cause one type of AE. Paraneoplastic neurological syndromes are usually associated with malignant cancers; however, patients can present with PAs but without cancer. In this study, we evaluated the diagnostic significance of PAs in adult Japanese patients with AE. We analyzed the medical records of all patients who visited our epilepsy clinic and were intensively evaluated for AE between April 2021 and October 2022. Patients with new-onset seizures or worsening acute or subacute seizures who also showed prominent AE symptoms, such as memory impairment, emotional lability, and involuntary movements, were enrolled. Data from the PA panel, including anti-amphiphysin (AMPH), CV2, paraneoplastic Ma antigen 2 (PNMA2), Ri, Yo, Hu, recoverin, SRY-related HMG-box gene 1 (SOX1), titin, zic4, glutamate decarboxylase 65 (GAD65), and Tr/DNER antibodies, were evaluated. Of 32 patients who were investigated, 6 (19.0%; 2 males, age: 38.0 ± 18.0 years) were positive for PAs (anti-AMPH: 1, PNMA2: 1, Yo: 1, recoverin: 2, SOX1: 1). No patients had malignant tumors. Intravenous high-dose methylprednisolone was administered to four patients and was effective in three. Thus, we conclude that approximately one-fifth of AE cases are attributable to PAs, even though there are no signs of malignant tumors, in adult epilepsy clinics in Japan.Keywords: paraneoplastic neurological syndromes, paraneoplastic antibodies, autoimmune encephalitis, epilepsy, acute symptomatic seizures, malignant tumor